KOMPOSISI FITOPLANKTON YANG TERDAPAT DI PERAIRAN BATANG PALANGKI KABUPATEN SIJUNJUNG (Universitas PGRI Sumatera Barat, 2012)
ABSTRACTPhytoplankton is water plant which floats freely and float away in water andable to photosynthesis. Phytoplankton has important role since it become foodfor animals are life in that water, such as fish and insect. Morever, phytoplanktonis able to influence the quality of water. There are some houses, livestock marketand farmland. Water of Batang Palangki river is used to fulfill daily needs, meansof gold mining, sand, bathing place for livestock and fish catching. A researchhas been done in Batang Palangki river. Its purpose is to know the phytoplanktoncomposition in Batang Palangki river. This research was conducted by usingdescriptive survey method which chose four research stations that is station Isettlement area, station II farm, station III gold mining area and station IV postarea of gold mining. Sample was selected in 3 spots for each station, namely left,right and center of river. Parameter which was measured was abundance, relativedensity, frequency and relative frequency, and quality parameter of water whichwas measured was temperature, pH, the flow of speed, DO, and CO2. From theresult of this research, it was found that the phyotoplankton composition was 4classes, 4 ordo, 9 families and 13 genus. Total abundance was 24,68 individu/l,abundance is highest in station II was 8,34 individu/l, and then station I was 7,98individu/l, station IV was 4,93 individu/l and station III was 3,43 individu/l. Classthat highest abundance was Bacillariophyceae, was 16,55 individu/l and minimallow was Euglenophyceae, was 0,46 individu/l. Genus that highest abundance wasNavicula, was 4,78 individu/l and minimal low was Phacus was 0,46 individu/l.Key word: water pollution, composition, phytoplankton